Prevalence of posterior crossbite among pacifier users: a study in the deciduous dentition Prevalência de mordida cruzada posterior em usuários de chupeta: um estudo na dentadura decídua - Helio Scavone-Junior; Rívea Inês Ferreira; Tadeu Evandro Mendes; Flávio Vellini Ferreira (Sociedade Brasileira de Pesquisa Odontológica, 2007)
The aim of this study was to evaluate the prevalence of posterior crossbite among children whose pacifier-sucking habit persisted until different ages. Children aged 3 to 6 years were randomly selected from public preschools in São Paulo, SP, Brazil. Their mothers were asked to complete a questionnaire on non-nutritive sucking behaviors. The sample consisted of 366 children assigned to 2 groups: control (n = 96) and pacifier users (n = 270). Pacifier users were further assigned to 3 subgroups, according to the age of habit persistence: P1 - until 2 years of age; P2 - between 2 and 4 years of age; and P3 - between 4 and 6 years of age. One dentist assessed the children for occlusal relationships through clinical examination. Associations between the age interval of habit discontinuation and the prevalence of posterior crossbite were analyzed using the chi-square test (p < 0.05). The prevalence of posterior crossbite was significantly higher among pacifier users (20.4%), compared to control children (5.2%), p < 0.01. Unilateral posterior crossbite was more prevalent than bilateral crossbite among pacifier users (9.8% versus 3.6%). Functional posterior crossbites were diagnosed in 3.1% of the control children and 7% of the pacifier users. The frequencies of posterior crossbite were notably high for children in the 3 pacifier subgroups, P1, P2, and P3, corresponding to 17.2%, 16.9%, and 27.3%, respectively. The high prevalence of posterior crossbite may be associated with pacifier-sucking habits that persisted after 2 years of age. O objetivo deste estudo foi avaliar prevalência de mordida cruzada posterior em crianças com hábito de sucção de chupeta que persistiu até diferentes idades. Crianças dos 3 aos 6 anos de idade foram aleatoriamente selecionadas de pré-escolas públicas em São Paulo, SP, Brasil. Solicitou-se às mães que respondessem a um questionário sobre hábitos de sucção não-nutritivos. A amostra consistiu de 366 crianças distribuídas em 2 grupos: controle (n = 96) e usuários de chupeta (n = 270). Os usuários de chupeta foram, então, separados em 3 subgrupos de acordo com a idade de persistência do hábito: P1 - até 2 anos de idade; P2 - entre 2 e 4 anos de idade e P3 - entre 4 e 6 anos de idade. Um cirurgião-dentista avaliou a oclusão das crianças por exame clínico. As associações entre intervalo de interrupção do hábito e prevalência de mordida cruzada posterior foram analisadas pelo teste Qui-Quadrado (p < 0,05). A prevalência de mordida cruzada posterior foi significativamente mais elevada em usuários de chupeta (20,4%), em comparação às crianças controles (5,2%), p < 0,01. A mordida cruzada posterior unilateral foi mais prevalente do que a bilateral em usuários de chupeta (9,8% versus 3,6%). As mordidas cruzadas posteriores funcionais foram diagnosticadas em 3,1% das crianças controles e 7% dos usuários de chupeta. As freqüências de mordida cruzada posterior foram notavelmente elevadas nos 3 subgrupos de usuários de chupeta, P1, P2 e P3, correspondendo a 17,2%, 16,9% e 27,3%, respectivamente. A alta prevalência de mordida cruzada posterior pode estar associada com hábitos de sucção de chupeta que persistiram além dos 2 anos de idade.